Determinants of Price of Mustard Seed and Mustard Oil in Domestic Markets of India - Meena, Dinesh Chand; Singh, O. P.; Kumari, Maina (Indian Journal of Marketing, 2015)
India imports about half of its domestic consumption needs of edible oils. Among the different edible oilseeds grown in India, mustard occupies an important position as a large proportion of the Indian population consumes it as a vegetable oil. The farmers' decision regarding area allocation under oilseed crops is largely influenced by the prices of oilseeds. The study attempted to find the determinants of price of mustard seed and mustard oil in the domestic markets of India. A multiple linear regression analysis was fitted for the time series data. The results revealed that there was a positive and significant relationship between prices of sesame seed and mustard seed as well as between prices of soya oil and mustard oil. Therefore, it was concluded that sesame seed and soya oil were the close substitutes of the mustard seed and mustard oil respectively in the selected markets.